O ensino-aprendizagem de alunos surdos no ensino médio em classe de ensino regular - Sudré, Elaine Candido (2008)
This work is situated in the Applied Linguistics area, and more specifically in a context of continuing education for language teachers. As an ILCAE group researcher I focused on the process of teaching-learning and development of Deaf students during Portuguese classes in main stream classrooms. Considering the importance of mediated action in the teaching-learning process, I analyzed the resources that the teachers used to establish the interaction with their students in a context where there were neither interlocutors with satisfactory knowledge of LIBRAS, first language of Deaf students, nor interpreters. The research question was How does the teaching-learning of the Deaf student included in regular classroom happen? . After an initial interpretation of the data, I organized the analysis in four themes: teaching-learning, inclusion-exclusion, the Deaf, and language. Within a Socio-Historical-Cultural Theory perspective, data were analyzed based on what Bronckart (1999) defined as thematic content. The research was carried out in a critical interpretative methodology (Weber, 1987; Moita Lopes, 1996; Liberali & Liberali, mimeo). The discussion of data was based on Bakhtin s theoretical studies about language, on Vygotsky s perspectives about teaching and learning; and on Deaf Studies, by Skliar (1998). The research was developed in a State Elementary and High school of a city in the outskirts of São Paulo. The participants in the research process were: three Deaf students, three teachers (two Portuguese language teachers and a SAPE classroom teacher) and the other students who attend to the focused classroom. The data, consisting of: a) audio and video recording of 2 classes; b) audio recording of interviews with the participating teachers, c) researcher s observations; and d) field notes, were collected in 2007 and 2008. The discussions brought up by this study show that, currently, in regular main stream school, there has not been effective inclusion of the Deaf, and thus he/she has been put outside the teaching-learning process. Therefore, in the so called inclusive school, he/she has been all out of the conditions for his/her full development. In order to move toward an inclusion, in fact, it is necessary to restructure the way Brazilian State schools are constituted so that they could consider the linguistic, cultural, political demands for linguistic minorities, in this case, for Deaf community